Exploring the Role of Tattoo Discourse in Matotonan Village: Mentawai Tattoo Batik as an Effort to Preserve Tradition in Mentawai - Zulfa, Zulfa; Suraya, Rahmat Sewa; Ottman, Olsen (ppjbsip, 2024)
In the remote islands of North Pagai, South Pagai, Sipora, and Siberut, the ancient art of tattooing is on the verge of extinction. However, amidst this cultural decline, a unique endeavor emerges in the heart of Mentawai: the preservation of tattoos through the intricate art of Mentawai tattoo batik. This qualitative ethnographic study delves into the depths dicourse of Mentawai tattoo batik, illuminating its significance in the preservation of Mentawai's rich tattoo heritage. Through meticulous observations across the four islands of Mentawai and in-depth interviews with tattoo owners, particularly the revered Sikerei who lead the sacred Lia rituals, this research uncovers the profound narrative woven within each tattoo motif. In Matotonan Village, once vibrant with tattoo culture, youth no longer hold tattoos in high regard, risking the loss of this ancient tradition. Yet, amidst this cultural shift, Mentawai elders embark on a noble mission: to immortalize the sacred symbols of their ancestors by transferring Mentawai tattoo motifs onto clothing. This symbolic gesture not only safeguards the legacy of Mentawai tattoos but also ensures their transmission to future generations. For the Mentawai people, tattoos transcend mere body art; they embody the sacred connection between humanity and the natural world of Mentawai. As efforts to preserve these timeless symbols gain momentum, batik adorned with Mentawai tattoo motifs emerges as a beacon of hope, igniting a revival of cultural pride and heritage in the heart of Mentawai. Through the production of tattoo motif batik as a burgeoning home industry, the legacy of Mentawai tattoos finds new life, promising to endure for generations to come.